Role of FKBP5 in emotion processing: results on amygdala activity, connectivity and volume - Holz, Nathalie E.; Rietschel, Marcella; Meyer-Lindenberg, Andreas; Banaschewski, Tobias; Brandeis, Daniel; Laucht, Manfred (Brain structure & function, 2014)
Accumulating evidence suggests a role of FKBP5, a co-chaperone regulating the glucocorticoid receptor sensitivity, in the etiology of depression and anxiety disorders. Based on recent findings of altered amygdala activity following childhood adversity, the present study aimed at clarifying the impact of genetic variation in FKBP5 on threat-related neural activity and coupling as well as morphometric alterations in stress-sensitive brain systems. Functional magnetic resonance imaging during an emotional face-matching task was performed in 153 healthy young adults (66 males) from a high-risk community sample followed since birth. Voxel-based morphometry was applied to study structural alterations and DNA was genotyped for FKBP5 rs1360780. Childhood adversity was measured using retrospective self-report (Childhood Trauma Questionnaire) and by a standardized parent interview assessing childhood family adversity. Depression was assessed by the Beck Depression Inventory. There was a main effect of FKBP5 on the left amygdala, with T homozygotes showing the highest activity, largest volume and increased coupling with the left hippocampus and the orbitofrontal cortex (OFC). Moreover, amygdala-OFC coupling proved to be associated with depression in this genotype. In addition, our results support previous evidence of a gene-environment interaction on right amygdala activity with respect to retrospective assessment of childhood adversity, but clarify that this does not generalize to the prospective assessment. These findings indicated that activity in T homozygotes increased with the level of adversity, whereas the opposite pattern emerged in C homozygotes, with CT individuals being intermediate. The present results point to a functional involvement of FKBP5 in intermediate phenotypes associated with emotional processing, suggesting a possible mechanism for this gene in conferring susceptibility to stress-related disorders.